Coal clearance system at Zondagsfontein Colliery ? Synopsis - P. Mogodi (The Southern African Institute of Mining and Metallurgy, 2010)
The purpose of the project was to propose a coal clearance system (coal transportation system from the mining face to the plant) that could be used for the planned underground operations at Zondagsfontein Colliery. Components of the current coal clearance system were overlooked during feasibility studies. Subsequent studies of the coal clearance system revealed that the combined capacity of the two trunk belts does not match that of the shaft (main) belt. As a result production downtimes will be encountered due to bottlenecks in the system. Ways of addressing this challenge were analysed by weighing both advantages and disadvantages and ultimately a surge bin option was selected. Belt conveyor simulations were conducted in order to determine the optimum capacity of the surge bin. The configuration of the surge bin in relation to the two trunk belts was chosen by considering development cost, advantages, and disadvantages of each option. It was concluded and recommended that a 500 tonnes capacity surge bin is required to remove the bottleneck from the system.